Role of topical cyclosporine in prevention of pterygium recurrence, after primary excision. - Ahmed, Munawar (Pakistan Journal of Ophthalmology, 2021)
Role of topical cyclosporine in prevention of pterygium recurrence, after primary excision. Purpose: To evaluate the effect of cyclosporine on pterygium recurrence after primary excision Study Design: Non randomized prospective comparative study. Place and Duration of Study: The study was conducted in the department of Ophthalmology Liaquat University of Medical and Health Sciences Jamshoro from 2015 to 2017 Material and Methods: One hundred and thirty eyes of 65 patients having bilateral pterygium, at least 2mm encroaching on the cornea, were randomly selected for study. After informed consent patient was seen on slit lamp, the dimensions of pterygium was measured. The eye with more pterygium was selected for post-operative cyclosporine and was named as cyclo- eye and fellow eye was selected for simple excision and was named as non-cyclo eye. Immediate post-operative treatment was tobramycin dexamethasone eye ointment twice and moxifloxacine eye drops three times daily until corneal epithelium was restored, followed by moxifloxacine and Cyclosporine eye drops twice daily until complete healing of ocular surface occurred and then cyclosporine 0.05% alone once daily in the evening up to three months. In the fellow eye tobramycin dexamethasone eye ointment and moxifloxacine eye drops were used for complete healing time followed by tears alone three times for three months. Recurrence was defined as 1mm encroachment of pterygium on the cornea. Follow up was done for six months. Results: Fifty-three patients who completed 6 months follow were only included in the results. In cyclo-eyes recurrent pterygium was observed only in 04(07.55%) and in non-cyclo eyes recurrence was observed in 23(43.40%). Therefore, cyclosporine was able to reduce pterygium recurrence further in 19(35.85%) eyes, but healing time increased. Mean healing time in cyclo-eyes 21.1354 days and in non-cyclo-eyes 15.0213 days. Standard deviation in cyclo-eyes 1.3412 and in non-cyclo-eyes 1.0413. P-value was 0.002 and 0.004 respectively. Conclusion: Cyclosporine is effective in reducing the recurrence rate of pterygium. Key words: Pterygium, cyclosporine, recurrence